Analysis of CO2 emission reduction, energy and economy interactions in Turkey using Buems - Macro - Günel, Gizem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Growth in the world’s population and the economy, together with the rapid urbanization lead to a dramatic increase in energy demand. Among all energy sources, the most rapid consumption growth occurs in renewable energy which is followed by nuclear energy. The Turkish Ministry of Energy and Natural Resources (MENR) recently has released new projects under the Renewable Energy Resource Area (YEKA) scheme and announced intentions for three nuclear power plants by 2030. However, fossil fuels are expected to dominate the world’s energy demand in the near future, although fossil fuels are the largest contributors to climate change. As a result of this, energy modeling plays a key role in climate change mitigation and has been a widely used tool for energy planning in the recent past decades. This thesis aims to take advantages of both top-down and bottom-up energy models by proposing a model which defines a linkeage between the energy, the economy and the environment for the Turkish energy system. In this regard, Boğaziçi University Energy Modeling System (BUEMS) which has been developed under a project for the Scientific Technology and Research Council of Turkey (TUBİTAK, 2018), has been calibrated according to the latest Turkish energy sector data, and is used for the bottom-up structure and the Macro model that has been proposed in this thesis is used for the top-down structure. BUEMS and Macro models are together referred to as Boğaziçi University Energy Modeling System together with a Macroeconomic Model (BUEMS-MACRO). In this study, the current energy system of Turkey is taken as a Base scenario. Based on Base scenario, different policy scenarios have been carried out for both BUEMS and BUEMS-MACRO model and the results of policy scenarios are compared with the Base scenario.
Keywords: Renewable energy sources -- Turkey.